Perencanaan Sistem Penyaliran Tambang Batubara PT. Rajawali Internusa Jobsite PT. Indah Jaya Abadi Pratama, Lahat, Sumatera Selatan - Dimas Andrianto; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2019)
High rainfall at the planned mine site can hamper mining operations in achieving the production target of 500,000 MT / year. Planning of a mine drainage system is needed which is well reviewed technically and also the costs arising from the making of the mine drainage system. Analysis of daily rainfall data in research locations in 2008-2017 by using the gumbel distribution, obtained planned rainfall of 105.09 mm / day for the 2-year return period. Based on the results of the study, it was found that runoff discharge entering the mine was 7092 m3 / hour. The incoming water is accumulated into the sump which is then pumped out towards the open channel. Based on the total pump head of 100,824 and the ideal pumping capability, the type of pump used is Multiflo MF-420 with the recommended operating speed of 1300 RPM resulting in a discharge of 1000 m3 / hour. The dimensions of the open channel that will be used are in the form of trapezium because it is easier to make and maintain. Settling pond that will be made in zigzag shape with a length of 75 m, width of    35 m and depth of 5 m. The total cost that must be budgeted for in making sump, open channel and settling pond is Rp. 1,106,257,200. Keywords: Production,Rainfall,drainage,Pump,Budgeted